Stability in postcolonial African states - Bueya, Emmanuel (Lexington Books, 2018)
Despite support from Western states and international organizations, many postcolonial African states are far from being stable. This book uses a multidisciplinary approach with a theoretical ground from which the author explores the notions of structures and agents, how they affect the instability of states, and how stability can be achieved.